THE IMPACT OF THE COVID-19 PANDEMIC ON THE IMPLEMENTATION OF EMPOWERING THE ROLE OF WOMEN IN WEST JAVA - Kania, Ikeu; Stiaji, Iwan Ridwan; Astuti, Retno Sunu; Rohaeni, Nani; Yudiardi, Dodi (Jurnal Analisa Sosiologi, 2021)
The Covid-19 pandemic has changed the fabric of people's lives, including women's lives. The concentration of various activities at home as a result of the policies taken by the government to prevent the spread of Covid 19 indirectly increases the work burden of women who are among the vulnerable groups. The role of women as individuals and social beings has decreased, resulting in disruption of the system in their social environment. This condition was also triggered by the inadequate women's empowerment program launched by the government by diverting the availability of funds for the Covid-19 response program. The purpose of this study was to analyze the impact of not implementing women's empowerment programs during the Covid-19 pandemic. A qualitative approach with data collection techniques through literature study, observation, and interviews with various relevant government agencies, activists and volunteers, and women's groups affected by Covid-19 in West Java is the method used in this research. The results showed that several program activities such as the role of women in development, budget absorption, family resilience, family economic life, and the socialization of the healthy and prosperous program during the Covid-19 pandemic had changed a lot. This shows that the Covid-19 Pandemic had a negative impact on the Implementation of Empowering the Role of Women in West Java. Therefore, it is necessary to have a special strategy that can accommodate the implementation of programs in the field of Women's Empowerment in the new era (post-Covid-19), one of which is through program redesign and policy advocacy that leads to technical implementation and advocacy of women's empowerment programs in West Java.Â Keywords: Women's Empowerment, Program Redesign, Family Resilience, Covid-19AbstrakPandemi Covid-19 telah merubah tatanan kehidupan masyarakat termasuk kehidupan perempuan. Terpusatnya berbagai kegiatan di rumah sebagai akibat kebijakan yang diambil pemerintah dalam mencegah penyebaran Covid 19 secara tidak langsung menambah beban pekerjaan perempuan yang termasuk kelompok rentan. Peran perempuan sebagai individu dan mahluk social mengalami penurunan yang berakibat terganggunya sistem di lingkungan sosialnya. Kondisi ini juga dipicu oleh kurang optimalnya Program pemberdayaan perempuan yang telah dicanangkan oleh pemerintah dengan pengalihan ketersediaan dana untuk program penanggulan Covid-19. Tujuan penelitian ini untuk menganalisis dampak tidak terlaksananya program pemberdayaan perempuan dimasa pandemi Covid-19. Pendekatan kualitatif dengan teknik pengumpulan data melalui studi pustaka, observasi dan wawancara dengan berbagai instansi pemerintah terkait, aktivis dan relawan, dan kelompok perempuan yang terdampak Covid-19 di Jawa Barat merupakan metode yang digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa beberapa program kegiatan seperti peran perempuan dalam pembangunan, penyerapan anggaran, ketahanan keluarga, kehidupan ekonomi keluarga dan sosialisasi program sehat sejahtera dimasa pandemi Covid-19 ini banyak sekali mengalami perubahan. Hal ini menunjukkan bahwa adanya Pandemi Covid-19 berdampak negatif terhadap Pelaksanaan Pemberdayaan Peran Perempuan di Jawa Barat. Oleh karena itu, perlu adanya strategi khusus yang dapat mengakomodasi pelaksanaan program-program di bidang Pemberdayaan Perempuan di masa tatanan baru (pasca Covid-19), salah satunya dengan adanya redesain program dan advokasi kebijakan yang mengarah pada teknis pelaksanaan dan advokasi program pemberdayaan perempuan di Jawa Barat.Â Kata Kunci : Pemberdayaan Perempuan, Redesain Program, Ketahanan Keluarga, Covid-19